2018
DOI: 10.21873/invivo.11288
|View full text |Cite
|
Sign up to set email alerts
|

Fat-forming Solitary Fibrous Tumor of the Kidney – A Case Report and Literature Review

Abstract: Fat-forming solitary fibrous tumor (SFT) is a rare soft tissue tumor. Herein, we reported a 30-year-old woman was found to have a solid mass measuring 60×45 mm in the right kidney on an abdominal computed tomography scan. The tumor was well-circumscribed and composed of cellular nodules with the classic SFT admixed with clusters and lobules of mature adipocytes. Immunohistochemistry staining showed that the tumor cells were diffusely and strongly positive for CD34 and Bcl-2, focally and weakly positive for CD9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A few studies showed that pelvic [27,30,41], abdominal [27,42], and pleural [27,40,43] SFTs tend to be larger than tumors appearing in other locations, and extrapleural SFTs may show potentially malignant behavior [44], especially those with limb localization [45]. Generally, over the years, SFTs have been described in various localizations, including the liver [46,47], kidney [48][49][50], pancreas [23,51,52], sigmoid colon [31], mesocolon [14], omentum [53,54], urinary bladder [55], caecum wall [56], mesorectum [41], prostate [57], spermatic cord [58], testis [59], scrotum [60], female gynecological tract, especially the vulva [61,62], vagina [63], breast [64][65][66], heart and pericardium [33,67,68], epicardium [69], pulmonary artery [70], trachea [71], larynx [32,72], tongue [15], salivary glands [73]<...…”
Section: Anatomical Locationmentioning
confidence: 99%
“…A few studies showed that pelvic [27,30,41], abdominal [27,42], and pleural [27,40,43] SFTs tend to be larger than tumors appearing in other locations, and extrapleural SFTs may show potentially malignant behavior [44], especially those with limb localization [45]. Generally, over the years, SFTs have been described in various localizations, including the liver [46,47], kidney [48][49][50], pancreas [23,51,52], sigmoid colon [31], mesocolon [14], omentum [53,54], urinary bladder [55], caecum wall [56], mesorectum [41], prostate [57], spermatic cord [58], testis [59], scrotum [60], female gynecological tract, especially the vulva [61,62], vagina [63], breast [64][65][66], heart and pericardium [33,67,68], epicardium [69], pulmonary artery [70], trachea [71], larynx [32,72], tongue [15], salivary glands [73]<...…”
Section: Anatomical Locationmentioning
confidence: 99%
“…Solitary fibrous tumors (SFTs) were reported for the first time by Wagner et al [ 1 ] in 1870. As hemangiopericytomas, SFTs are usually benign and arise from mesenchymal spindle cells, typically of the pleura.…”
Section: Introductionmentioning
confidence: 99%